The association of polymorphisms in the ovine PPARGC1B and ZEB2 genes with body weight in Hu sheep. Issue 1 (1st February 2022) - Zhang, Deyin; Zhang, Xiaoxue; Li, Fadi; La, Yongfu; Li, Guoze; Zhang, Yukun; Li, Xiaolong; Zhao, Yuan; Song, Qizhi; Wang, Weimin
Abstract: The aims of this study were to analyze the effects of PPARGC1B and ZEB2 polymorphisms on the body weight of Hu sheep. DNA sequencing and KASPar technologies were used to detect single nucleotide polymorphisms (SNPs) within the PPARGC1B and ZEB2 genes of Hu sheep ( n = 207). Two synonymous mutations, g.300 G > A and g.645 C > T, were detected in PPARGC1B and ZEB2, respectively. The body weights of sheep were recorded at 80, 100, 120, 140, 160 and 180-days, and associations between these polymorphisms and body weight changes were analyzed. Association analysis demonstrated that the polymorphisms in PPARGC1B and ZEB2 significantly associated with body weight ( p < 0.05). At the g.300 G > A locus, individuals with the GG genotype had significantly higher body weight than those with the AA genotype, and at the g.645 C > T locus, individuals with the TT genotype had significantly higher body weight than those with the TC genotype. Individuals with both polymorphisms exhibited significantly different growth ( p < 0.05). These data suggest that polymorphisms in the PPARGC1B and ZEB2 genes can be used as candidate molecular markers for the breeding of desirable growth traits in Hu sheep.